(untitled) (Scientific journal of the Fergana State University, 2023)
This article highlights the problem of discourse, which is one of the main problems of pragmatic and cognitive linguistics, recognized as new trends in modern linguistics. At the same time, the study of a particular individual discourse as a separate object of research has been studied. The concepts of discourse and text, as well as their interrelationships with each other, were analyzed, and in this regard, the views expressed in Uzbek, Russian and world linguistics were studied as an object of research. In linguistics, it was originally understood as a connected and agreed consequence in a sentence or speech, but in modern linguistics it is characterized by its interpretation as a complex communicative phenomenon.